1956
DOI: 10.1246/bcsj.29.115
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding Effect on the Fluorescence of π-Electron System

Abstract: 1. The absorption and fluorescence spectra of α-, β- naphthols and related compounds were measured in various mixed solvents in connection with the hydrogen bonding phenomena. The observed spectral shifts of absorption and fluorescence spectra, which were almost the same (∼30 Å), could be solely attributed to the hydrogen bonding effect. 2. It was found that the fluorescence intensity becoms stronger by hydrogen bonding when dioxane and acetic acid esters other than ethylchloroacetate are used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

1957
1957
1993
1993

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Some aspects of this effect on the fluorescence of naphthols were studied by the present authors [3]. Nagakura and Gouterman [l] have demonstrated that both ~-and fl-naphthols form a quite strong hydrogen bond with triethylamine (TEA) in the excited Franck-Condon state and the equilibrium ground state.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Some aspects of this effect on the fluorescence of naphthols were studied by the present authors [3]. Nagakura and Gouterman [l] have demonstrated that both ~-and fl-naphthols form a quite strong hydrogen bond with triethylamine (TEA) in the excited Franck-Condon state and the equilibrium ground state.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, the same circumstance holds when the hydrogen bond is formed between nitrogen heterocycles as proton acceptors and fluorescers, and proton donors such as phenol, naphthol, aniline and pyrrole [8]. In both of these cases, the hydrogen bond is closely related to the 7r-electron systems of the donors and acceptors, and the observed strong fluorescence quenching has been interpreted as due to the delocalization of ~-electrons through the hydrogen bond, in the excited electronic state [3,8]. The lowest ionization potentials of TEA and pyridine are 7.50 ev (n-orbital) [9] and 9.26 ev (Tr-orbital) [10], respectively.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations